AKTIVITAS LITERASI TANPA PERPUSTAKAAN: STUDI KASUS SEKOLAH DASAR NEGERI 2 SUKASADA, BULELENG, BALI: Aktivitas Literasi - Kadek Tirta Darma Putra; Dr. Luh Putu Sri Ariyani, S.S., M.Hum.; Santana Sembiring, S.Sos., M.A. (Universitas Pendidikan Ganesha, 2026)
This study aims to determine the types of literacy activities carried out by Sukasada 2 Public Elementary School, as well as the difficulties they face when they do not have a formal school library. This study uses a qualitative descriptive approach, where observation, interviews, and document studies are used as data collection methods. The principal, teachers, book collection managers, and education staff are the research informants. The results show that students of Sukasada 2 Public Elementary School can still develop literacy skills through 15-minute reading activities before class starts, reading during breaks, reading together every Friday, and having a reading corner in each class. Literacy activities still face several challenges. Among them are collection management that is not yet effectively organized; limited space and supporting facilities; and a lack of human resources needed to manage literacy activities. The school utilizes reading corners, book rotation between classes, and active teacher involvement in teaching and getting students into reading habits. This study shows that by utilizing available facilities and getting active support from the school, literacy activities can be carried out without a formal school library.